Bending and vibration analysis of multi-folding laminate composite plate using finite element method - Thinh, Tran Ich; Binh, Bui Van; Tu, Tran Minh (Vietnam Journal of Mechanics, 2012)
This paper deals with the bending and vibration analysis of multi-folding laminate composite plate using finite element method based on the first order shear deformation theory (FSDT). The algorithm and Matlab code using eight nodded rectangular isoparametric plate element with five degrees of freedom per node were built for numerical simulations. In the numerical results, the effect of folding angle on deflections, natural frequencies and transient displacement response for different boundary conditions of the plate were investigated.